1990
DOI: 10.1016/0248-4900(90)90369-e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a series of homologous α,ω‐dimethylaminoalkanes on cell proliferation: binding and uptake of putrescine by a human glioblastoma cell line (U251) in culture

Abstract: The first step of polyamine uptake is the binding of polyamines to the cell membrane. In order to characterize the specificity of the putrescine binding sites at the surface of the glioblastoma cells (U251), we have carried out competition experiments between putrescine bound to latex microspheres and vizualized by scanning electron microscopy and a series of N,N'-tetramethyl-alpha,omega-diaminoalkanes. N,N'-tetramethyl-1,4-butanediamine (N,N'-tetramethylputrescine) and higher homologs inhibit the latex putres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Douaud et al (1997) observed cytotoxic activities of dimethylsilane polyamine analogues, suggesting that the higher lipophilicity of these drugs compared to natural polyamines allows them to bind to hydrophobic groups in the vicinity of anionic binding sites. The importance of the hydrophobic character of polyamine analogues on proliferation of U251 human glioblastoma cells was also proposed by Quemener et al (1990). They demonstrated increasing antiproliferative activity of putrescine analogues (N,N'-tetramethyl-α,ω-diaminoalkanes) with an increasing CH 2 -chain length, suggesting that the enhanced hydrophobicity is related to the growth-inhibitory effect.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Douaud et al (1997) observed cytotoxic activities of dimethylsilane polyamine analogues, suggesting that the higher lipophilicity of these drugs compared to natural polyamines allows them to bind to hydrophobic groups in the vicinity of anionic binding sites. The importance of the hydrophobic character of polyamine analogues on proliferation of U251 human glioblastoma cells was also proposed by Quemener et al (1990). They demonstrated increasing antiproliferative activity of putrescine analogues (N,N'-tetramethyl-α,ω-diaminoalkanes) with an increasing CH 2 -chain length, suggesting that the enhanced hydrophobicity is related to the growth-inhibitory effect.…”
Section: Discussionmentioning
confidence: 92%
“…An increase in hydrophobicity of polyamine analogues compared to natural polyamines has been suggested to play an important role for their antiproliferative properties (Quemener et al 1990;Douaud et al 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Specific binding sites with high affinity for polyamines on cell membrane have been demonstrated using latex-bound polyamines (23,24). Whether the antibody displays such non-covalently bound polyamines or only polyamines bound to the membrane proteins as a product of a transglutaminase-catalyzed reaction is still under question.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to show that cell membranes bind putrescine (Put) bound to latex microspheres [15]. Structural analogs of putrescine, the homologous ~,w-dimetbylaminoaminoalkanes, conapete with Put-latex for the binding sites, if their carbon chain contains four to seven C-atoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…We were able to show that cell membranes bind putrescine (Put) bound to latex microspheres [15]. Structural analogs of putrescine, the homologous ~,w-dimetbylaminoaminoalkanes, conapete with Put-latex for the binding sites, if their carbon chain contains four to seven C-atoms [15]. These analogs have an antiproli ferative action on the U251 cell line, whereas the lower homologue with two carbon atoms (N,N'-tetramethyl-l,2-ethanediamine) does not compete for binding, but it reduces more than the other homologues the uptake of putrescine [15] and spermidine [10].…”
Section: Introductionmentioning
confidence: 99%